2018
DOI: 10.1103/physreve.97.020701
|View full text |Cite
|
Sign up to set email alerts
|

Shape control of surface-stabilized disclination loops in nematic liquid crystals

Abstract: Recent studies on topological defects in conventional and active nematic liquid crystals have revealed their potential as sources of advanced functionality whereby the collective behavior of the constituent molecules or cells is controlled. On the other hand, the fact that they have high energies and are metastable makes their shape control a nontrivial issue. Here, we demonstrate stabilization of arbitrary-shaped closed disclination loops with 1/2 strength floating in the bulk by designing the twist angle dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…[23][24][25] The resulting topological structures with or without disclinations, identified as torons or hopfions, can be stable, although homeotropic alignment in the bulk has a lower elastic energy. The structures studied by the Ozaki group 22,26 can also be considered as solitons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] The resulting topological structures with or without disclinations, identified as torons or hopfions, can be stable, although homeotropic alignment in the bulk has a lower elastic energy. The structures studied by the Ozaki group 22,26 can also be considered as solitons.…”
Section: Introductionmentioning
confidence: 99%
“…In their experiments Sunami et al use a similar circular photo-alignment pattern, but with only a 180°rotation of the azimuthal angle and therefore they find only one structure with a single disclination ring. 26 In the following we discuss the technology for the fabrication process, the patterned alignment and the cell assembly, show polarization optical microscopy (POM) images of the structures, present finite-element Q-tensor simulations for the director configuration and corresponding transmission simulations based on a beam propagation method (BPM).…”
Section: Introductionmentioning
confidence: 99%
“…This ability was exploited in recent years to create an artificial web of disclination lines (in non-equilibrium conditions) [21], and to stabilize 2D diffractive structures with intricate bulk director configurations demonstrating symmetry breaking and regions with pronounced non-planar director orientation in the bulk [22][23][24][25]. In general, patterned planar photo-alignment offers valuable possibilities to study the formation of (twist) disclination lines, their interaction and their annihilation when the alignment patterns are well designed [21][22][23][24][25][26][27][28][29][30]. When a different azimuthal angle is imposed at corresponding locations at the top and bottom substrate, a position dependent twist in the bulk can occur.…”
Section: Introductionmentioning
confidence: 99%
“…When a different azimuthal angle is imposed at corresponding locations at the top and bottom substrate, a position dependent twist in the bulk can occur. However, for some combinations of alignment patterns at the substrates, the topology at the interfaces requires either the creation of disclinations in the bulk or regions with vertical director orientation [15,[23][24][25][26][27][28][29][30]. We recently demonstrated for different alignment configurations that surface induced twist conflicts are often elegantly resolved, without the need for singular disclination lines, by introducing a region with vertical director orientation in the bulk of the device [15,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Therefore, significant efforts have recently been dedicated to developing techniques for generating topological defects with designable structures. [39][40][41][42][43][44][45][46] For example, Yoshida and co-workers demonstrated suspended disclination loops by designing twist angle distribution [40,41] and 3D disclination networks by shifting defect patterns at the top and bottom surfaces. [42] Yokoyama et al demonstrated stable webs of freestanding disclinations by using designed alignment patterns on two confining surfaces.…”
mentioning
confidence: 99%